Navigating gender and sexuality in the classroom: Narrative insights from students and educators - McEntarfer, Heather Killelea (Routledge, 2016)
Gender identity and sexuality play crucial roles in the educational experiences of students, parents, and teachers. Teacher education must more directly address the ways that schools reflect and reproduce oppressive gender norms, working to combat homophobia, transphobia, heteronormativity, and gendered expectations in schools. This volume examines teacher candidates’ experiences with gender and sexuality in the classroom, offering insight and strategies to better prepare teachers and teacher educators to support LGBTQ youth and families. This volume addresses the need for broader, more in-depth qualitative data describing teacher candidates’ responses to diversity in the classroom (including gender, sexuality, race, class and religion). By using pedagogical tools such as narrative writing and positioning theory, teacher candidates explore these issues to better understand their own students’ narratives in deeply embodied ways. This book calls for schools to be places where oppression, in all its complexity, is explored and challenged rather than replicated.
Keywords: LGBTQIA2+; approches et analyses; discipline; formations; hétérosexisme; identités LGBTQIA2+; intersectionnalité; outils; outils didactiques; privilèges; pédagogie; religion; sciences de l'éducation; sexualité; systèmes d'oppressions; thématiques

The pedagogical practices of Québec high school teachers relative to sexual diversity - Richard, Gabrielle (Journal of LGBT Youth, 2015)
This article explores the ways in which teachers describe their pedagogical and intervention practices relative to sexual diversity in Québec (Canada). Three variables closely associated with teachers who report inclusive practices emerge: experiential training (based on the experience of a lesbian, gay, or bisexual [LGB] teacher), contact training (from close acquaintance with LGB individuals), and professional training. These factors impact the probability that a teacher will refer to homosexuality, intervene when homophobic incidents occur to deconstruct prejudices, and become the confidant of LGBQ students. Results are discussed based on research on minority teachers and on the roles of straight allies in education.
Keywords: EDI; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; discipline; diversité sexuelle; formations; homophobie; hétérosexisme; identités LGBTQIA2+; outils; québec; ressource en ligne; régions géographiques; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; travail; école secondaire

PEP: programme express protection. Programme et guide pédagogique. - Caron, Françoise; Otis, Joanne; Lafontaine, Michel; Godin, Gaston; Baril, Patrice (Régie régionale de la santé et des services sociaux (Montérégie)/Direction de la santé publique, de la planification et l'évaluation, 1999)
Keywords: 1900-1999; 1990-1999; Infections transmisibles sexuellement et par le sang; VIH; amériques; formations; outils; prévention; périodes historiques; québec; ressource en ligne; régions géographiques; santé; sexualité; thématiques; école secondaire